ANALYSIS OF STORY PROBLEMS BY APPLYING THE PROBLEM BASED LEARNING BASED ON NEWMAN'S ERROR ANALYSIS - Yuliana Yuliana; Marhan Taufik; Reni Dwi Susanti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
his study aims to describe the application of the PBL learning model in mathematics learning, to find out the types of errors that students make in solving math story problems based on Newman's analysis, and what factors are the causes of student errors in solving math story problems. The subjects of this research were students of class VII. The type of research used in this research is descriptive qualitative. Data collection techniques used in this research are observation, written tests, and interviews. The results showed that learning with the application of the PBL model with NEA on the rectangular material went very well during the three meetings that went very well, as indicated by the implementation of each of these learning steps during the learning process going well, this indicates that student activities when the learning process by applying the PBL learning model with the NEA went very well. The error analysis based on the NEA shows that the most mistakes made by students were errors in writing the final answer. This was due to students' mistakes in working on the previous stage and also students who did not write conclusions, the lowest error made by students was transformation errors.